Determinants of ICT Tools Accessibility by Farmers in Bihar - Anand, Shreya; Prakash, Satya; Singh, A.K (Indian Journal of Extension Education, 2022)
The economy of a developing country like India is mostly dependent on performance of agriculture sector, and its growth highlights the need of transferring relevant timely information to farmers. Information and communication technology (ICT) plays an important role in this regard. India is progressively using ICT into its national development strategy and implementing tactics for widespread promotion in order to develop the country into a knowledge-rich, e-learning society. Present study was conducted during the year 2019 to determine the degree of access and use of ICTs by farmers and its determinants covering a random sample of 100 farmers in Katihar and Samastipur districts of Bihar. Majority of farmers were young and educated up to high school, mostly accessed mobile phone amongst the ICT tools. Farmers’ diversified occupation, education, annual income, farming system/allied agricultural activities, mass media exposure, and extension contact were positively and significantly correlated with accessibility of ICT tools. Regression model revealed that selected farmers’ attributes explained about 61 per cent variation in accessibility of ICT tools by the farmers.
Keywords: ICT tools; Accessibility; Farmers; Attributes